Impact of the COVID-19 Pandemic on Prenatal Care Utilization at a Public Hospital - Boguslawski, Shae M.; Joseph, Naima T.; Stanhope, Kaitlyn K.; Ti, Angeline J.; Geary, Franklyn H.; Boulet, Sheree L. (American Journal of Perinatology, 2022)
Objective The aim of the study is to compare rates of prenatal care utilization before and after implementation of a telehealth-supplemented prenatal care model due to the coronavirus disease 2019 (COVID-19) pandemic.Study Design Using electronic medical record data, we identified two cohorts of pregnant persons that initiated prenatal care prior to and during the COVID-19 pandemic following the implementation of telehealth (from March 1, 2019 through August 31, 2019, and from March 1, 2020, through August 31, 2020, respectively) at Grady Memorial Hospital. We used Pearson's Chi-square and two-tailed t-tests to compare rates of prenatal care utilization, antenatal screening and immunizations, emergency department and obstetric triage visits, and pregnancy complications for the prepandemic versus pandemic-exposed cohorts.Results We identified 1,758 pregnant patients; 965 entered prenatal care prior to the COVID-19 pandemic and 793 entered during the pandemic. Patients in the pandemic-exposed cohort were more likely to initiate prenatal care in the first trimester (46.1 vs. 39.0%, p = 0.01), be screened for gestational diabetes (74.4 vs. 67.0%, p <0.001), and receive dating and anatomy ultrasounds (17.8 vs. 13.0%, p = 0.006 and 56.9 vs. 47.3%, p <0.001, respectively) compared with patients in the prepandemic cohort. There was no difference in mean number of prenatal care visits between the two groups (6.9 vs. 7.1, p = 0.18). Approximately 41% of patients in the pandemic-exposed cohort had one or more telehealth visits. The proportion of patients with one or more emergency department visits was higher in the pandemic-exposed cohort than the prepandemic cohort (32.8 vs. 12.3%, p < 0.001). Increases in rates of labor induction were also observed among the pandemic-exposed cohort (47.1 vs. 38.2%, p <0.001).Conclusion Rates of prenatal care utilization were similar before and during the COVID-19 pandemic. However, pregnant persons receiving prenatal care during the pandemic entered care earlier and had higher utilization of certain antenatal screening services than those receiving prenatal care prior to the pandemic.Key Points
Keywords: COVID-19; prenatal care; telehealth; antenatal screening